Motivational Drivers of Shopee PayLater Usage: Economic, Psychological, and Social Perspectives Among Communities in Sinjai Regency, Indonesia - Rahmawati; Muslimin kara; Sumarin; Jamaluddin Majid; Muhamatsakree Manyunu (Yayasan Amerta Insan Unggul, 2026)
This study examines the growing use of digital credit services by focusing on Shopee PayLater adoption in Sinjai Regency, Indonesia, a region where limited financial access and shifting consumption patterns have increased reliance on flexible payment systems. Despite the rapid expansion of Buy-Now-Pay-Later services, little research has explored the multidimensional motivations driving their use in semi-rural communities. The study aims to identify the economic, psychological, and social motivational drivers behind Shopee PayLater usage among residents of Sinjai. A qualitative research design was employed, using purposive sampling to select community members from diverse occupations, with primary data collected through in-depth, semi-structured interviews. Thematic analysis was used to classify and interpret recurring patterns across interview transcripts. Findings revealed three dominant motivational themes: economic motivations, particularly the convenience of deferred payment and financial flexibility in meeting urgent or strategic needs; psychological motivations, including emotional satisfaction, perceived modernity, and increased self-confidence from participating in contemporary consumption trends; and social motivations, such as peer influence, community norms, and the desire to avoid social exclusion in digital shopping practices. These results show that PayLater adoption is driven not merely by financial necessity but by a combination of emotional and social dynamics embedded in everyday life. The study contributes to the understanding of digital credit behavior in developing regions and offers practical implications for policymakers and financial service providers seeking to design responsible, inclusive, and culturally attuned digital financing solutions.